Abu Suhbah and As-Siba'i's Rebuttal of the Inkar Sunnah Group (Thought Analysis Study) - Abdul Rohim; Engkos Kosasih; Muhammad Al Mighwar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Purpose and topic This research examines the objections of Abu Suhbah and as-Syiba'I to Abu Royah and Taufiq Sidiq regarding the position of the sunnah as the basis of Islamic teachings. The method used in this paper is a qualitative descriptive method by collecting library data to then analyze its contents. The results of this analysis found that the modern inkar sunnah understanding spread by Abu Royah and Taufiq Sidiq according to the author's analysis is based on a deep ignorance of the function of the sunnah in Islamic teachings. With this research, readers will understand that the sunnah is not only an explanation of what is in the Qur'an, but also has its own role in determining religious law, besides that readers will also realize that in every era there must always be groups who want to shake one of the pillars of the source of religion, namely the Prophet's sunnah.